Improvement in the Power Conversion Efficiency of Bulk Heterojunction Photovoltaic Device via Thermal Postannealing of Subphthalocyanine:C70 Active Layer - Chih-Chien Lee; Shun-Wei Liu; Ching-Wen Cheng; Wei-Cheng Su; Chia-Chang Chou; Chun-Feng Lin; Chin-Ti Chen (International Journal of Photoenergy)
The authors report an efficient organic photovoltaic device based on subphthalocyanine (SubPc):C70 bulk heterojunction (BHJ) via the postannealing treatment. The power conversion efficiency is improved from 4.5% to 5.5% due to the increase in short-circuit current density (JSC) from 8.8 to 12.7 mA/cm2 with the expense of decreased fill factor from 52% to 42%. From external quantum efficiency measurements, the spectral shape-independent enhancement over the entire spectrum suggests that the increased JSC mainly originates from improved charge collection efficiency. To confirm this inference, the hole and electron mobilities in the BHJ are estimated from the space-charge limited current, showing improved transport properties at the optimum temperature. Moreover, the morphologic change is also studied as a function of annealing temperature. A larger grain size is observed with increasing temperature due to the phase separation of SubPc and C70. However, at higher temperatures the strong aggregation of C70 molecules may interrupt the pathway of SubPc, resulting in hindered charge transport and, hence, reduced JSC.